EFEKTIVITAS GAYA PEMASARAN BAKAR-BAKAR DUIT OLEH E-COMMERCE DI INDONESIA - Nurlaily, Liafatra; Kuntari, Oktarini (JURNAL STIE SEMARANG, 2024)
This study aims to determine the effectiveness of marketing strategies using the style of burning money by e-commerce to achieve the goals of increasing data, people’s purchasing power using e-commerce, and changing the behaviour of Indonesian people towards digitalization. The literature study method was used to conduct this research due to limited time and resources to conduct case studies or collect data through interviews with e-commerce visitors. The results of the study show the effectiveness of the money-burning marketing style in increasing the number of e-commerce users, increasing the amount of annual e-commerce revenue, and increasing the percentage of activity in the use of e-commerce by internet users in Indonesia.